PERKEMBANGAN GENJEK DI DESA SRAYA BALI - I Nengah Muliana (Gelar : Jurnal Seni Budaya, 2012)
The object of this paper is Genjek in the village of Sraya, Karangasem regency. The focus is on the development of form and function. The aim is to uncover why art Genjek at Sraya village had been developed, and what factors are causing.  This paper begins with an overview of data about the digging community, especially those related to regional situation, livelihood, education, and arts potential. This is done to get an idea of   the extent to which it affects the development of Genjek.  Genjek existence before 1996 and after 1996 are described in detail so clearly visible changes. This method can be known who is responsible, why the change was made  , how the impact of those changes on the form and functionGenjek in Sraya village. The data obtained for this paper using interviews, audio visual recordings, and writings in the form of a book or otherwise. The data is then broken down, identified, classified, and analyzed, so it gets a conclusion. Appropriate perspective of this paper, it is used to analyze the data change theory.                                                                     Changes will occur in any art when assessed was no longer relevant to society. Society as the owner arts have a considerable role to the process of change. Changes in the arts because of certain impulses both from within and from outside the arts are the arts. Encouragement of the arts can be extremely diverse forms ranging from the influence of individuals in the group, to the desire or communal group. The results of the analysis conducted in this study concluded that the changes in the village Sraya Genjek occurs because growth mindset people are influenced by internal and external factors. Key words : Genjek, development, community Pengantar